Answer:
y+4=-2(x-4)
Simplified- y=-2x+4
Step-by-step explanation:
y+4= -2(x-4)
y+4= -2x+8
-4. -4
y=-2x+4
A boat travels 33 miles downstream in 4 hours. The return trip takes the boat 7 hours. Find the speed of the boat in still water.
Answer:
Speed of the boat in still water = 6.125 miles/hour
Step-by-step explanation:
We are given that a boat travels 33 miles downstream in 4 hours and the return trip takes the boat 7 hours.
We are to find the speed of the boat in the still water.
Assuming [tex]S_b[/tex] to be the speed of the boat in still water and [tex]S_w[/tex] to be the speed of the water.
The speeds of the boat add up when the boat and water travel in the same direction.
[tex]Speed = \frac{distance}{time}[/tex]
[tex]S_b+S_w=\frac{d}{t_1}=\frac{33 miles}{4 hours} [/tex]
And the speed of the water is subtracted from the speed of the boat when the boat is moving upstream.
[tex]S_b-S_w=\frac{d}{t_2}=\frac{33 miles}{7 hours} [/tex]
Adding the two equations to get:
[tex]S_b+S_w=\frac{d}{t_1}[/tex]
+ [tex]S_b-S_w=\frac{d}{t_2} [/tex]
___________________________
[tex]2S_b=\frac{d}{t_1} +\frac{d}{t_2}[/tex]
Solving this equation for [tex]S_b[/tex] and substituting the given values for [tex]d,t_1, t_2[/tex]:
[tex]S_b=\frac{(t_1+t_2)d}{2t_1t_2}[/tex]
[tex]S_b=\frac{(4 hour + 7hour)33 mi}{2(4hour)(7hour)}[/tex]
[tex]S_b=\frac{(11 hour)(33mi)}{56hour^2}[/tex]
[tex]S_b=6.125 mi/hr[/tex]
Therefore, the speed of the boat in still water is 6.125 miles/hour.
Answer:
[tex]6.48\frac{mi}{h}[/tex]
Step-by-step explanation:
Let' call "b" the speed of the boat and "c" the speed of the river.
We know that:
[tex]V=\frac{d}{t}[/tex]
Where "V" is the speed, "d" is the distance and "t" is the time.
Then:
[tex]d=V*t[/tex]
We know that distance traveled downstream is 33 miles and the time is 4 hours. Then, we set up the folllowing equation:
[tex]4(b+c)=33[/tex]
For the return trip:
[tex]7(b-c)=33[/tex] (Remember that in the return trip the speed of the river is opposite to the boat)
By solving thr system of equations, we get:
- Make both equations equal to each other and solve for "c".
[tex]4(b+c)=7(b-c)\\\\4b+4c=7b-7c\\\\4c+7c=7b-4b\\\\11c=3b\\\\c=\frac{3b}{11}[/tex]
- Substitute "c" into any original equation and solve for "b":
[tex]4b+\frac{3b}{11} =33\\\\4b+\frac{12b}{11}=33\\\\\frac{56b}{11}=33\\\\b=6.48\frac{mi}{h}[/tex]
Given the function f(x) = 2x – 1 and the linear function g(x), which function has a greater value when x = 3?
A.f(x) is greater.
B.g(x) is greater.
C.f(x) and g(x) are the same when x=3
D.g(x) is undefined when x=3
Answer:
Option B. g(x) is greater
Step-by-step explanation:
step 1
Find the value of f(x) when the value of x is equal to 3
we have
f(x)=2x-1
substitute the value of x=3
f(3)=2(3)-1=5
step 2
Find the value of g(x) when the value of x is equal to 3
Observing the graph
when x=3
g(3)=7
step 3
Compare the values
f(x)=5
g(x)=7
so
g(x) > f(x)
g(x) is greater
Answer:
Correct option is:
B. g(x) is greater
Step-by-step explanation:
Firstly, we find the value of f(x) when x=3
f(x)=2x-1
substitute the value of x=3
f(3)=2×3-1=5
On observing the graph, we see that g(x)=7 when x=3
Now, on Comparing the values of f(x) and g(x) when x=3
f(3)=5
g(3)=7
so, g(x) > f(x) when x=3
So, Correct option is:
B. g(x) is greater
PLEASE HELP!!! Given the functions, f(x) = 6x + 2 and g(x) = x - 7, perform the indicated operation. When applicable, state the domain restriction. (f/g)(x)
To find (f/g)(x) with f(x) = 6x + 2 and g(x) = x - 7, one must divide f(x) by g(x). The domain restriction occurs because division by zero is not defined, so we exclude the x value that makes g(x) zero, which is x = 7.
Explanation:To perform the indicated operation (f/g)(x) with the given functions f(x) = 6x + 2 and g(x) = x - 7, we need to divide the function f(x) by the function g(x). This operation is equivalent to finding the quotient of the two functions, which is expressed as:
(f/g)(x) = f(x)/g(x) = (6x + 2)/(x - 7)
The domain restriction occurs when the denominator, g(x), is equal to zero since division by zero is undefined. So we must find the value of x for which g(x) = 0. Since g(x) = x - 7, setting this equal to zero gives us:
x - 7 = 0 → x = 7
Therefore, the domain of the function (f/g)(x) is all real numbers except for x = 7, because at x = 7 the function is undefined. The domain of (f/g)(x) can be expressed as ℜ - {7}, where ℜ represents the set of all real numbers.
one x-intercept for a parabola is at the point (2, 0). use the quadratic formula to find the other x-intercept for the parabola defined by y=x^2-3x+2
Answer:
Step-by-step explanation:
There are 3 ways to find the other x intercept.
1) Polynomial Long Division.
Divide x^2 - 3x + 2 by the binomial x - 2, because by the Factor Theorem if a is a root of a polynomial then x - a is a factor of said polynomial.
2) Just solving for x when y = 0, by using the quadratic formula.
[tex]x^2 - 3x + 2 = 0\\x_{12} = \frac{3 \pm \sqrt{9 - 4(1)(2)}}{2} = \frac{3 \pm 1}{2} = 2, 1[/tex].
So the other x - intercept is at (1, 0)
3) Using Vietta's Theorem regarding the solutions of a quadratic
Namely, the sum of the solutions of a quadratic equation is equal to the quotient between the negative coefficient of the linear term divided by the coefficient of the quadratic term.
[tex]x_1 + x_2 = \frac{-b}{a}[/tex]
And the product between the solutions of a quadratic equation is just the quotient between the constant term and the coefficient of the quadratic term.
[tex]x_1 \cdot x_2 = \frac{c}{a}[/tex]
These relations between the solutions give us a brief idea of what the solutions should be like.
What is the solution to the system of equations graphed below?
- 3x+2
y = 5x + 28
Answer:
(-3.25, 11.75)Step-by-step explanation:
We only need two points to plot the graph of each equation.
[tex]y=-3x+2\\\\for\ x=0\to y=-3(0)+2=0+2=2\to(0,\ 2)\\for\ x=1\to y=-3(1)+3=-3+2=-1\to(1,\ -1)\\\\y=5x+28\\\\for\ x=-4\to y=5(-4)+28=-20+28=8\to(-4,\ 8)\\for\ x=-6\to y=5(-6)+28=-30+28=-2\to(-6,\ -2)[/tex]
Look at the picture.
Read the coordinates of the intersection of the line (solution).
15.5
tons
155 tons =how many
pounds
Determine the scale factor of 5 to 10
there's a scale factor of two!
five times two is ten.
hope this helps! :) xx
The equation of a circle in general form is x2+y2+20x+12y+15=0 . What is the equation of the circle in standard form?
ANSWER
[tex]{(x + 10)}^{2} + {(y + 6)}^{2} = 121[/tex]
EXPLANATION
The equation of the circle in general form is given as:
[tex] {x}^{2} + {y}^{2} + 20x + 12y + 15 = 0[/tex]
To obtain the standard form, we need to complete the squares.
We rearrange the terms to obtain:
[tex] {x}^{2} + 20x + {y}^{2} + 12y = - 15 [/tex]
Add the square of half the coefficient of the linear terms to both sides to get:
[tex]{x}^{2} + 20x +100 + {y}^{2} + 12y + 36 = - 15 + 100 + 36[/tex]
Factor the perfect square trinomial and simplify the RHS.
[tex]{(x + 10)}^{2} + {(y + 6)}^{2} = 121[/tex]
This is the equation of the circle in standard form.
how to divide (x^2+5x-6)/(x-1)
Answer:
x+6
Step-by-step explanation:
Let's see if the numerator is factorable.
Since the coefficient of x^2 is 1 (a=1), all you have to do is find two numbers that multiply to be -6 (c) and add up to be 5 (b).
Those numbers are 6 and -1.
So the factored form of the numerator is (x+6)(x-1)
So when you divide (x+6)(x-1) by (x-1) you get (x+6) because (x-1)/(x-1)=1 for number x except x=1 (since that would lead to division by 0).
Anyways, this is what I'm saying:
[tex]\frac{(x+6)(x-1)}{(x-1)}=\frac{(x+6)\xout{(x-1)}}{\xout{(x-1)}}[/tex]
[tex]x+6[/tex]
Find the area of quadrilateral ABCD. [Hint: the diagonal divides the quadrilateral into two triangles.]
A. 26.47 units²
B. 28.53 units²
C. 27.28 units²
D. 33.08 units²
Answer:
B) 28.53 unit²
Step-by-step explanation:
The diagonal AD divides the quadrilateral in two triangles:
Triangle ABDTriangle ACDArea of Quadrilateral will be equal to the sum of Areas of both triangles.
i.e.
Area of ABCD = Area of ABD + Area of ACD
Area of Triangle ABD:
Area of a triangle is given as:
[tex]Area = \frac{1}{2} \times base \times height[/tex]
Base = AB = 2.89
Height = AD = 8.6
Using these values, we get:
[tex]Area = \frac{1}{2} \times 2.89 \times 8.6 = 12.43[/tex]
Thus, Area of Triangle ABD is 12.43 square units
Area of Triangle ACD:
Base = AC = 4.3
Height = CD = 7.58
Using the values in formula of area, we get:
[tex]Area = \frac{1}{2} \times 4.3 \times 7.58 = 16.30[/tex]
Thus, Area of Triangle ACD is 16.30 square units
Area of Quadrilateral ABCD:
The Area of the quadrilateral will be = 12.43 + 16.30 = 28.73 units²
None of the option gives the exact answer, however, option B gives the closest most answer. So I'll go with option B) 28.53 unit²
What is the slope of st.line xcosa+ysina=p? ( Find by using derivative)
Answer:
Assume that [tex]a[/tex] and [tex]p[/tex] are constants. The slope of the line will be equal to
[tex]\displaystyle -\frac{\cos{(a)}}{\sin{(a)}} = \cot{(a)}[/tex] if [tex]\sin{a} \ne 0[/tex];Infinity if [tex]\sin{a} = 0[/tex].Step-by-step explanation:
Rewrite the expression of the line to express [tex]y[/tex] in terms of [tex]x[/tex] and the constants.
Substract [tex]x\cdot \cos{(a)}[/tex] from both sides of the equation:
[tex]y \sin{(a)} = p - x\cos{(a)}[/tex].
In case [tex]\sin{a} \ne 0[/tex], divide both sides with [tex]\sin{a}[/tex]:
[tex]\displaystyle y = - \frac{\cos{(a)}}{\sin{(a)}}\cdot x+ \frac{p}{\sin{(a)}}[/tex].
Take the first derivative of both sides with respect to [tex]x[/tex]. [tex]\frac{p}{\sin{(a)}}[/tex] is a constant, so its first derivative will be zero.
[tex]\displaystyle \frac{dy}{dx} = - \frac{\cos{(a)}}{\sin{(a)}}[/tex].
[tex]\displaystyle \frac{dy}{dx}[/tex] is the slope of this line. The slope of this line is therefore
[tex]\displaystyle - \frac{\cos{(a)}}{\sin{(a)}} = -\cot{(a)}[/tex].
In case [tex]\sin{a} = 0[/tex], the equation of this line becomes:
[tex]y \sin{(a)} = p - x\cos{(a)}[/tex].
[tex]x\cos{(a)} = p[/tex].
[tex]\displaystyle x = \frac{p}{\cos{(a)}}[/tex],
which is the equation of a vertical line that goes through the point [tex]\displaystyle \left(0, \frac{p}{\cos{(a)}}\right)[/tex]. The slope of this line will be infinity.
Latesha’s mother puts $85 in Latesha’s lunch account at school. Each day Latesha uses $3 from her account for lunch. The table below represents this situation. Latesha’s Lunch Account Day Amount Left in Account ($) 0 $85 1 2 3 4 5 How much is left in Latesha’s lunch account after she has had lunch for 5 days?
A.$15
B.$67
C.$70
D.82
Answer:
=70$
Step-by-step explanation:
The total in her account at day zero =85$
Lunch for five days= 3$×5
=15$
Total in her account= Initial amount - Expenditure on lunch
=85$-15$
=70$
The balance in Latesha's Lunch Account after having lunch for five day=70$
Bianca has a stamp collection of 5 cent stamps and 7 cent stamps. She has 3 less 7 cent stamps as 5 cent stamps. If the collection has a face value of 87 cents, how many of each does she have?
She has ____ 5 cent stamps and ____ 7 cent stamps.
Answer:
She has 9 5 cent stamps and 6 7 cent stamps.
Step-by-step explanation:
Let the number of five cent stamps be represented by F and the number of seven cent stamps be represented by S.
The difference between the number of five cent and seven cent stamps is 3
F-S=3
The sum of the collection from each type of stamp is 87 cents
5F+7S=87
Let us solve the equations simultaneously.
F-S=3
5F+7S=87
Using substitution method,
F= 3+S
5(3+S)+7S=87
15+5S+7S=87
12S=87-15
12S=72
S=6
F=3+S
=3+6=9
Therefore the number of five cent stamps is 9 and seven cent stamps is 6.
Answer:
Number of 5 cent stamps = 9
Number of 7 cent stamps = 6
Step-by-step explanation:
We are given that Bianca has a stamp collection of 5 cent stamps and 7 cent stamps in which there are 3 less 7 cent stamps as 5 cent stamps.
If the total face value of stamps is 87 cents, we are to find the number of stamps of each value.
Assuming [tex]t[/tex] to be the number of 5 cent stamps and [tex]s[/tex] to be the 7 cent stamps so we can write it as:
[tex]0.05t+0.07s=0.87[/tex] --- (1)
[tex]s=t-3[/tex] --- (2)
Substituting this value of [tex]s[/tex] from (2) in (1):
[tex]0.05t+0.07(t-3)=0.87[/tex]
[tex]0.05s+0.07t-0.21=0.87[/tex]
[tex]0.12t=1.08[/tex]
[tex]t=9[/tex]
Number of 5 cent stamps = 9
Number of 7 cent stamps = 9 - 3 = 6
Write 1.47 as a mixed number or a fraction In simplest form
Answer:
[tex]\frac{147}{100}[/tex]
Step-by-step explanation:
This is the answer because 147 ÷ 100 = 1.47
the number of three-digit numbers with distinct digits that be formed using the digits 1,2,3,5,8 and 9 is . The probability that both the first digit and the last digit of the three-digit number are even numbers .
Answer:
a)120
b)6.67%
Step-by-step explanation:
Given:
No. of digits given= 6
Digits given= 1,2,3,5,8,9
Number to be formed should be 3-digits, as we have to choose 3 digits from given 6-digits so the no. of combinations will be
6P3= 6!/3!
= 6*5*4*3*2*1/3*2*1
=6*5*4
=120
Now finding the probability that both the first digit and the last digit of the three-digit number are even numbers:
As the first and last digits can only be even
then the form of number can be
a)2n8 or
b)8n2
where n can be 1,3,5 or 9
4*2=8
so there can be 8 three-digit numbers with both the first digit and the last digit even numbers
And probability = 8/120
= 0.0667
=6.67%
The probability that both the first digit and the last digit of the three-digit number are even numbers is 6.67% !
1.
[tex]6\cdot5\cdot4=120[/tex]
2.
[tex]|\Omega|=120\\|A|=2\cdot4\cdot1=8\\\\P(A)=\dfrac{8}{120}=\dfrac{1}{15}\approx6.7\%[/tex]
Use the intercepts from the graph below to determine the equation of the function.
A) 4x-3y=12
B) -4x-3y=12
C) 4x-3y=-12
D) -4x+3y=-12
ANSWER
C) 4x-3y=-12
EXPLANATION
The intercept form of a straight line is given by:
[tex] \frac{x}{x - intercept} + \frac{y}{y - intercept} = 1[/tex]
From the the x-intercept is -3 and the y-intercept is 4.
This is because each box is one unit each.
We substitute the intercepts to get:
[tex] \frac{x}{ - 3} + \frac{y}{4} = 1[/tex]
We now multiply through by -12 to get
[tex] - 12 \times \frac{x}{ - 3} + - 12 \times \frac{y}{4} = 1 \times - 12[/tex]
[tex]4x - 3y = -12[/tex]
The correct choice is C.
write a compound inequality that represents each situations all real numbers that are greater than -8 but less than 8
Answer:
[tex]-8 < x < 8[/tex]
Step-by-step explanation:
Your compound inequality will include two inequalities.
These are:
x > -8
x < 8
Put your lowest number first, ensuring that your sign is pointed in the correct direction.
[tex]-8 < x[/tex]
Next, enter your higher number, again making sure that your sign is pointing in the correct direction.
[tex]-8 < x < 8[/tex]
Answer:
-8 < r < 8
Step-by-step explanation:
Let r = real number
Greater than >
r>-8
less than <
r <8
We want a compound inequality so we combine these
-8 < r < 8
What type of angles are 1 and 5?
vertical
supplementary
corresponding
complementary
Answer:
corresponding
Step-by-step explanation:
Answer:
Corresponding
Step-by-step explanation:
I like to call corresponding angles, the copy and paste angles because you can copy and paste the top intersection over the bottom intersection; the angles that lay down on top of each other are the corresponding angles. 1 and 5 do this.
how much is 2 plus 9
For this case we must represent the following expression algebraically, in addition to indicating its result:
"2 plus 9"
So, we have:
[tex]2 + 9 =[/tex]
By law of the signs of the sum, we have that equal signs are added and the same sign is placed:
[tex]2 + 9 = 11[/tex]
ANswer:
11
Find the values of k for which the quadratic equation 2x^2 − (k + 2)x + k = 0 has real and equal roots.
Answer:
k = 2
Step-by-step explanation:
If the roots are real and equal then the condition for the discriminant is
b² - 4ac = 0
For 2x² - (k + 2)x + k = 0 ← in standard form
with a = 2, b = - (k + 2) and c = k, then
(- (k + 2))² - (4 × 2 × k ) = 0
k² + 4k + 4 - 8k = 0
k² - 4k + 4 = 0
(k - 2)² = 0
Equate factor to zero and solve for k
(k - 2)² = 0 ⇒ k - 2 = 0 ⇒ k = 2
Answer:
k = 2Step-by-step explanation:
A quadratic equation has two equal real roots if a discriminant is equal 0.
[tex]ax^2+bx+c=0[/tex]
Discriminant [tex]b^2-4ac[/tex]
We have the equation
[tex]2x^2-(k+2)x+k=0\to a=2,\ b=-(k+2),\ c=k[/tex]
Substitute:
[tex]b^2-4ac=\bigg(-(k+2)\bigg)^2-4(2)(k)\qquad\text{use}\ (a+b)^2=a^2+2ab+b^2\\\\=k^2+2(k)(2)+2^2-8k=k^2+4k+4-8k=k^2-4k+4\\\\b^2-4ac=0\iff k^2-4k+4=0\\\\k^2-2k-2k+4=0\\\\k(k-2)-2(k-2)=0\\\\(k-2)(k-2)=0\\\\(k-2)^2=0\iff k-2=0\qquad\text{add 2 to both sides}\\\\k=2[/tex]
if you are paid $5.50/hour for mowing yards, and you take 3 1/3 hours to mow a yard, how much money are you owed?
[tex]\bf \begin{array}{ccll} \$&hour\\ \cline{1-2} 5.5&1\\ x&3\frac{1}{3} \end{array}\implies \cfrac{5.5}{x}=\cfrac{1}{3\frac{1}{3}}\implies \cfrac{5.5}{x}=\cfrac{1}{\frac{3\cdot 3+1}{3}}\implies \cfrac{5.5}{x}=\cfrac{1}{\frac{10}{3}}\implies \cfrac{5.5}{x}=\cfrac{\frac{1}{1}}{\frac{10}{3}} \\\\\\ \cfrac{5.5}{x}=\cfrac{1}{1}\cdot \cfrac{3}{10}\implies \cfrac{5.5}{x}=\cfrac{3}{10}\implies 55=3x\implies \stackrel{\textit{about 18 bucks and 33 cents}}{\cfrac{55}{3}=x\implies 18\frac{1}{3}=x}[/tex]
Answer:
$18.3
Step-by-step explanation:
If you are paid $5.50/hour for mowing yards, and you take 3 1/3 hours to mow a yard, you should earn $18.3.
3 1/3 hours
$5.50 and hour
$5.50 x 3 = $16.5
$5.50 / 3 = $1.8
$16.5 + $1.8 = $18.3
Therefore, you are owed $18.3.
A football coach is trying to decide: when a team ahead late in the game, which strategy is better?
Answer:
regular
Step-by-step explanation:
1. look at table
notice regular and prevent defense have different wins but same total. 2. wins have more for regular so that's your answerAnswer:
The correct option is A)
P(Win|Regular)=0.76
P(Win|Prevent )=0.58
You are more likely to win by playing regular defense.
Step-by-step explanation:
Consider the provided table.
We need to find which strategy is better.
If team play regular defense then they win 38 matches out of 50.
[tex]Probability=\frac{\text{Favorable outcomes}}{\text{Total number of outcomes}}[/tex]
[tex]P(Win|Regular)=\frac{38}{50}[/tex]
[tex]P(Win|Regular)=0.76[/tex]
If team play prevent defense then they win 29 matches out of 50.
Thus, the probability of win is:
[tex]P(Win|Prevent )=\frac{29}{50}[/tex]
[tex]P(Win|Prevent )=0.58[/tex]
Since, 0.76 is greater than 0.58
That means the probability of winning the game by playing regular defense is more as compare to playing prevent defense.
Hence, the conclusion is: You are more likely to win by playing regular defense.
Thus, the correct option is A)
P(Win|Regular)=0.76
P(Win|Prevent )=0.58
You are more likely to win by playing regular defense.
PLEASE HELP AS FAST AS POSSIBLE PLEASE HELP PLEASE
Evaluate 0.00008 ÷ 640,000,000.
A) 1.25 × 10 -15
B) 1.25 × 10 -14
C) 1.25 × 10 -13
D) 1.25 × 10 -12
Answer:
0.00008 ÷ 640,000,000 means
8*10^-5 ÷ 6.4*10^8
so let's collect to simplify the operation
(8÷6.4)*(10^-12) -5-7=-12
then the answer becomes 1.25×10^-14 that is B
Answer:
option C
Step-by-step explanation:
Evaluate 0.00008 ÷ 640,000,000.
0.00008 can be written in standard notation
Move the decimal point to the end
so it becomes [tex]8 \cdot 10^{-5}[/tex]
for 640,000,000 , remove all the zeros and write it in standard form
[tex]64 \cdot 10^7[/tex]
Now we divide both
[tex]\frac{8 \cdot 10^{-5}}{64 \cdot 10^7}[/tex]
Apply exponential property
a^m divide by a^n is a^ m-n
[tex]\frac{8}{64} =0.125[/tex]
[tex]\frac{10^{-5}}{10^7}=10^{-12}[/tex]
[tex]0.125 \cdot 10^{-12}= 1.25 \cdot 10^{-13}[/tex]
Find the reciprocal of the expression.
The quantity 10 multiplied by b end of quantity divided by the quantity 2 multiplied by b plus 8 end of quantity.
A. Negative the quantity of the quantity 10 multiplied by b end of quantity divided by the quantity 2 multiplied by b plus 8 end of quantity end of quantity.
B. The quantity 2 multiplied by b plus 8 end of quantity divided by the quantity 10 multiplied by b end of quantity.
C. The quantity 10 multiplied by b plus 8 end of quantity divided by the quantity 2 multiplied by b end of quantity.
D. Negative the quantity of the quantity 2 multiplied by b plus 8 end of quantity divided by the quantity 10 multiplied by b end of quantity end of quantity.
Answer:
Option B
Step-by-step explanation:
we know that
To find the reciprocal of a fraction, flip the fraction.
Remember that
A number multiplied by its reciprocal is equal to 1
In this problem we have
[tex]\frac{10b}{2b+8}[/tex]
Flip the fraction
[tex]\frac{2b+8}{10b}[/tex] -----> reciprocal
therefore
The reciprocal is
The quantity 2 multiplied by b plus 8 end of quantity divided by the quantity 10 multiplied by b end of quantity.
Solve for x: 5 over x equals 4 over quantity x plus 3
5
3
−3
−15
Answer:
x = - 15
Step-by-step explanation:
The equation is [tex]\frac{5}{x}=\frac{4}{x+3}[/tex]
We now cross mulitply and do algebra to figure the value of x (shown below):
[tex]\frac{5}{x}=\frac{4}{x+3}\\5(x+3)=4(x)\\5x+15=4x\\5x-4x=-15\\x=-15[/tex]
Hence x = -15
Answer:
D
Step-by-step explanation:
PLEASE HURRY
WILL GIVE BRAINLIEST
What is the equation for the hyperbola shown?
Find the answer in the attachment.
The hyperbola's equation is x² / 3600 - y² / 121 = 1, centered at the origin (0,0). Its vertices are at (60,0), (-60,0) on the x-axis, and (0,11), (0,-11) on the y-axis.
To find the equation of the hyperbola, we need to determine its center and the distances from the center to the vertices along the x and y axes. The general equation of a hyperbola centered at (h, k) is given by:
(x - h)² / a² - (y - k)² / b² = 1
Where (h, k) is the center of the hyperbola, and 'a' and 'b' are the distances from the center to the vertices along the x and y axes, respectively.
In this case, since the hyperbola is symmetric along the x and y axes, the center is at the origin (0, 0). Also, we know the distance from the center to the vertices along the x-axis is 60 units (60 and -60) and along the y-axis is 11 units (11 and -11).
So, a = 60 and b = 11.
Now we can plug these values into the equation:
x² / (60)² - y² / (11)² = 1
Simplifying further:
x² / 3600 - y² / 121 = 1
And that's the equation of the hyperbola.
To know more about hyperbola:
https://brainly.com/question/19989302
#SPJ2
square root of 3 x^2 times square root of 4x
[tex]\bf \sqrt{3x^2}\cdot \sqrt{4x}\implies \sqrt{3x^2\cdot 4x}\implies \sqrt{12x^2x}\implies \sqrt{4\cdot 3\cdot x^2x} \\\\\\ \sqrt{2^2\cdot 3\cdot x^2x}\implies 2x\sqrt{3x}[/tex]
Tom has 8 toys each toy weighs either 20 grams or 40 grams or 50 grams he has a diffrent number of toys (at least one) of each weight What is the smallest possible total weight of Tom's toys
Answer:
110
Step-by-step explanation:
He said he had atleast 1 of each. Hope it helps.
The smallest possible total weight of Tom's toys is:
210 grams
Step-by-step explanation:It is given that:
Tom has 8 toys each toy weighs either 20 grams or 40 grams or 50 grams.
Also, he has a different number of toys (at least one) of each weight.
Now, the smallest possible weight of Tom's toy is such that:
He has one toy of 50 grams , one of 40 grams and the other's are of smallest weight i.e. 20 grams.
This means he has 6 toys of 20 grams.
One of 40 grams.
One of 50 grams.
Hence,
Total weight= 20×6+40+50
i.e.
Total weight= 120+90
i.e.
Total weight= 210 grams.
Need help with this problem h+-3=4 please
Answer:
h=7
Step-by-step explanation:
[tex]h+(-3)=4[/tex]
may be rewritten as
[tex]h-3=4[/tex]
as adding a negative is the same as subtracting a positive.
To solve, add 3 to both sides.
[tex]h-3=4\\h=7[/tex]
Answer:
h=7
Step-by-step explanation:
1) Add three to both sides
2) You should get h=7
What is the sum of the complex numbers below?
(5+7i)+(-2+6i)
A. -3 +13i
B. 3+13i
C. -3-13i
D. 3-13i
Answer:
B
Step-by-step explanation:
Given
(5 + 7i) + (- 2 + 6i ) ← remove parenthesis and collect like terms
= 5 + 7i - 2 + 6i
= 3 + 13i → B
The sum of the complex number is 3 + 13i.
Option B is the correct answer.
We have,
To find the sum of the complex numbers (5+7i) and (-2+6i), you can simply add the real parts together and add the imaginary parts together separately.
Real part: 5 + (-2) = 3
Imaginary part: 7i + 6i = 13i
Combining the real and imaginary parts, we get:
Sum = 3 + 13i
Therefore,
The sum of the complex number is 3 + 13i.
Learn more about expressions here:
https://brainly.com/question/3118662
#SPJ2